Studi tentang pelayanan terhadap kapal perikanan Di Pelabuhan Perikanan Pantai (PPP) Tumumpa Kota Manado (Study on Fishery Ship Service at Tumumpa Coastal fishing port (PPP) at Manado City) - Nikodemus Kirwelakubun; Mariana E. Kayadoe; Janny F. Polii; Frangky F. Kaparang; Fransisco P.T. Pangalila (Universitas Sam Ratulangi, 2018)
To achieve the purpose of fisheries development the most important thing to note is the development of fishing ports. This research is to assess the service of fishing vessel in PPP Tumumpa concerning: mooring service, loading and unloading service, port and shipping administration services.Â Primary data in this study were collected by conducting a direct survey to the PPP location. Data obtained from this study were analyzed by using qualitative analysis. The number of fishing vessels based in PPP Tumumpa are 166 ships, 41% of them are between 20-30 GT with 4,5-5,5 in breadths. With harbour length of 50 m, the number of fising vessels, berthing in the same time was only 8-9 ships. During 2016, the least number of ship visits was in February of 89 ships, and the most visits were in October of 233 ships. The mooring activity at PPP Tumumpa needed to queue for 2-3 days. The time required for the uploading and unloding activities is reasonable. The uploading and unloading activities at PPP Tumumpa were very disturbed by some facilities that were not in good condition. Fishery ship administration service in PPP Tumumpa has been running folowing the SOPs.keywords: fishing vessel, unloading and loading, fishing portÂ ABSTRAKUntuk mencapai tujuan pembangunan perikanan hal yang paling penting diperhatikan adalah pelabuhan perikanan. Penelitian ini untuk menilai pelayanan kapal perikanan di PPP Tumumpa menyangkut Â pelayanan tambat labuh, pelayanan bongkar-muat, pelayanan administrasi pelabuhan dan pelayaran. Data primer dikumpulkan dengan cara melakukan survei langsung ke lokasi PPP, data yang diperoleh dianalisis dengan menggunakan analisis kualitatif.Kapal perikanan yang berpangkalan di PPP Tumumpa sebanyak 166 buah, dan 41% diantaranya berbobot antara 20-30 GT dengan lebar kapal rata-rata 4,5-5,5 m. Dengan panjang dermaga 50 m, jumlah kapal yang dapat berlabuh secara bersamaan hanya sebanyak 8-9 unit. Selang tahun 2016 kunjungan kapal dan penerbitan SPB paling sedikit pada bulan Februari sebanyak 89 kapal dan paling banyak pada bulan Oktober sebanyak 233 kapal. Kegiatan tambat labuh di PPP Tumumpa membutuhkan waktu antre 2-3 hari. Waktu yang dibutuhkan tambat labuh dan melakukan aktivitas bongkar muat sudah sesuai. Kegiatan bongkar muat sangat terganggu karena beberapa fasilitas dalam keadaan rusak. Pelayanan administrasi kapal perikanan di PPP Tumumpa sudah berjalan sesuai tahapan pada SOP.Kata-kata kunci : kapal perikanan, bongkar-muat, pelabuhan perikanan